2018
DOI: 10.47102/annals-acadmedsg.v47n11p451
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Single and Double Cleavage-Stage Embryo Transfers, Single and Double Blastocyst Transfers in a South East Asian In Vitro Fertilisation Centre

Abstract: Introduction: This study investigated the differences in clinical pregnancy rate (CPR), live birth rate (LBR) and multiple pregnancy rate (MPR) between double cleavage-stage embryo transfers compared to single and double blastocysts stage embryo transfers in a single academic medical centre. Materials and Methods: This was a retrospective cohort study performed at the KK Women’s and Children’s Hospital In Vitro Fertilisation (KKIVF) Centre of all women who underwent fresh-cycle in vitro fertilisation/intracyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…The transfer of cleavage-stage embryos with different numbers of blastomeres due to inconsistent developmental speeds during the process of in vitro embryo culture affects clinical outcomes [ 3 , 4 , 6 , 11 ]. The extended culture of embryos after IVF to produce blastocysts for single blastocyst transfer has become an effective method of assisted pregnancy to reduce the rate of multiple pregnancies without reducing the clinical pregnancy rate compared with double cleavage-stage embryo transfer [ 12 , 13 ]. Several factors, including maternal age, fertilization mode and in vitro culture conditions, can affect the blastocyst formation rate of human embryos cultured in vitro [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transfer of cleavage-stage embryos with different numbers of blastomeres due to inconsistent developmental speeds during the process of in vitro embryo culture affects clinical outcomes [ 3 , 4 , 6 , 11 ]. The extended culture of embryos after IVF to produce blastocysts for single blastocyst transfer has become an effective method of assisted pregnancy to reduce the rate of multiple pregnancies without reducing the clinical pregnancy rate compared with double cleavage-stage embryo transfer [ 12 , 13 ]. Several factors, including maternal age, fertilization mode and in vitro culture conditions, can affect the blastocyst formation rate of human embryos cultured in vitro [ 14 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 A Singapore study by KK Women's and Children's Hospital In Vitro Fertilisation Centre similarly concluded that single-blastocyst transfers confer lower multiple pregnancy rates and should be offered as standard practice where possible. 8 Currently, only a third of our patients undergo eSET and only 1 embryo is transferred for first-time patients below 35 years old. Women above 35 years old are encouraged to transfer only 1 embryo.…”
mentioning
confidence: 99%
“…Kwek et al 12 reported that SBT had similar clinical pregnancy and live birth rates to those of DET. The present study showed that the clinical pregnancy and live birth rates in the DET group were signi cantly higher than those in the SBT group.…”
Section: Discussionmentioning
confidence: 97%